O inconsciente na relação processual: reflexões acerca da efetividade do devido processo legal - Berto, Alexandre Fontana (2021)
This research aimed to bring to the reflection of how unconscious psychic phenomena interfere in the procedural relationship and highlight that the legal system and legal science choose to disregard the interference of the unconscious basis in law. The verification, by the sciences of the mind, of the intensity and importance of the unconscious in human activity and the detection that the law has, in its essence, human affectation in its constitution, interpretation and transformation, makes it impossible to disregard the intense relationship between the unconscious and the legal activity. Starting from the most recurrent psychoanalytic theories about the unconscious, we chose, methodologically, to focus on the theoretical framework of Antonio Damásio and Jacques Lacan, specially to demonstrate the hypothesis according to which, both for neuroscience and for psychoanalysis, the unconscious is constituted from signifiers and affects positioned in memories and circumstances prior to the onset of their respective behaviors. The comparison of the psychoanalytical basis and neuroscience with the procedural legal relationship made us meditate on gaps in the main aspects of the controversial relationships and how the current due process of law is deeply affected by the unconscious, whether in relation to the delimitation of the claim, in the development of the evidential phase and mainly regarding of the results of the judgments that, currently constituted in the symbolic perspective, suffer great unconscious interference, without such intercessions being objectively detected, substantiated and explained by the justice system. The results obtained from the research reveal that, despite the procedural legal relationship being vigorously impacted by unconscious elements, there are no tools in the legal sciences or in the legal system itself capable of translating the relevance of this interference, which affects the lack of effectiveness in obtaining the jurisdictional benefit